The legal basis for the functioning of teaching hospitals in Poland: selected issues (Journal of Medical Science, 2017)
The teaching hospitals occupy a unique position in the health care system. The specific nature of teaching hospitals calls for a different legal regime from that governing other hospitals. Their activity includes not only the provision of health care, but also teaching, under- and postgraduate training, and conducting research and clinical trials. Teaching hospitals operate as autonomous public health care units endowed with legal personality, founded by institutions of higher education. This fact is not reflected in the provisions of generally applicable law, which lack regulations relating to the particular nature of the activity carried out by this type of health care entity.